2002
DOI: 10.1152/ajpgi.00431.2001
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous interleukin-10 modulates fibrosis and regeneration in experimental chronic pancreatitis

Abstract: Interleukin (IL)-10, a potent anti-inflammatory cytokine, limits the severity of acute pancreatitis and downregulates transforming growth factor (TGF)-beta release by inflammatory cells on stimulation. Proinflammatory mediators, reactive oxygen species, and TGF-beta can activate pancreatic stellate cells and their synthesis of collagen I and III. This study evaluates the role of endogenous IL-10 in the modulation of the regeneration phase following acute pancreatitis and in the development of pancreatic fibros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 41 publications
4
71
0
2
Order By: Relevance
“…Studies in other organs, including lung, heart, pancreas and liver, also showed IL-10 could suppress inflammatory response and thereby inhibit matrix remodeling and fibrosis process, even if fibrosis had developed. [31][32][33][34][35][36][37] Here, we provide direct evidence supporting the role of IL-10 in renal fibrosis by demonstrating that knockout of IL-10 leads to more severe inflammatory response and renal injury and fibrosis in the UUO model. In addition, we found that knockout of IL-10 enhanced activation of TGF-b/Smad3 and NF-kB pathways at days 7 and 14 after UUO, which are known to have central roles in the initiation and progression of renal inflammation and fibrosis through inducing a wide array of genes encoding pro-inflammatory cytokines, adhesion molecules, and chemokines in human and experimental models of kidney diseases.…”
Section: Interleukin-10 In Uuo Micementioning
confidence: 70%
See 1 more Smart Citation
“…Studies in other organs, including lung, heart, pancreas and liver, also showed IL-10 could suppress inflammatory response and thereby inhibit matrix remodeling and fibrosis process, even if fibrosis had developed. [31][32][33][34][35][36][37] Here, we provide direct evidence supporting the role of IL-10 in renal fibrosis by demonstrating that knockout of IL-10 leads to more severe inflammatory response and renal injury and fibrosis in the UUO model. In addition, we found that knockout of IL-10 enhanced activation of TGF-b/Smad3 and NF-kB pathways at days 7 and 14 after UUO, which are known to have central roles in the initiation and progression of renal inflammation and fibrosis through inducing a wide array of genes encoding pro-inflammatory cytokines, adhesion molecules, and chemokines in human and experimental models of kidney diseases.…”
Section: Interleukin-10 In Uuo Micementioning
confidence: 70%
“…9 The role of IL-10 in fibrosis has been also reported in other organs such as lung, heart and pancreas fibrosis. [10][11][12] The underlying mechanism of antifibrotic effects of IL-10 remains unclear, but it has been suggested that IL-10 can suppress extracellular matrix synthesis and inhibit key inflammatory pathways such as NF-kB. [13][14][15] In the context of kidney, IL-10 has been reported to effectively suppress the progression of acute and chronic renal damage in vivo.…”
mentioning
confidence: 99%
“…65,66 In conclusion, we were able to establish an immortal cell line from human pancreas, which is phenotypically and functionally indistinguishable from primary activated PSC with respect to the expression of stellate cell markers (vimentin, aSMA and GFAP) and their response to TGFb1 and PDGF treatment. Importantly, we were able to demonstrate that besides soluble factors, the matrix surrounding PSC plays a pivotal role in the maintenance of the activation process of PSC, as cultivation of activated PSC on a reconstituted basement membrane plus treatment with NAC was able to deactivate the cells, thus pointing to the possibility of an antifibrosis therapy in chronic pancreatitis.…”
Section: Deactivation Of Pancreatic Stellate Cells R Jesnowski Et Almentioning
confidence: 82%
“…Severity of cerulein induced pancreatitis was graded by a semi-quantitative scoring system as previously described. 19 Briefly, pancreatic sections, were investigated regarding parameters such as tissue architecture changes (graded as: 0=absent, 1=rare, 2=minimal (<10%), 3=moderate (<50%) and 4=major (>50%) of the total parenchyma affected), fibrosis (0 = absent, 2=only within areas, and 4=diffuse), glandular atrophy (0=absent, 1=minimal, 2=moderate, 3=major) and presence of pseudotubular complexes (0=absent, 1=minimal, 2=moderate, 3=major). These parameters were graded and a total score was calculated for each pancreatic specimen.…”
Section: Histological Analysis and Grading Of Pancreatic Lesionsmentioning
confidence: 99%